Evaluation of the effectiveness of antimicrobial stewardship interventions in paediatric patients with community-acquired pneumonia: impact on the length of hospital stay - Rafalskyi, Vladyslav; Khaitovych, Mykola (The Ukrainian Scientific Medical Youth Journal, 2025)
community-acquired pneumonia remains one of the leading causes of paediatric hospitalization worldwide, especially in resource-limited settings. Prolonged hospital stay imposes an additional burden on the healthcare system, negatively affects the psychological wellbeing of both the child and their family, increases the risk of hospital-acquired infections, and is associated with significant financial losses for households. Optimizing the duration of antibacterial therapy through antimicrobial stewardship programs enables the reduction of hospitalization length without compromising clinical outcomes. The aim of this study was to evaluate the effectiveness of a set of antimicrobial stewardship interventions implemented in clinical practice in paediatric patients with community-acquired pneumonia. A comparative analysis of medical records of children hospitalized in 2023 (before the interventions) and in 2025 (after the interventions) at a medical facility in Kyiv was conducted. A total of 138 cases were analysed (48 in 2023 and 90 in 2025). The interventions included the development and approval of a standard operating procedure (a set of instructions that helps standardise a process to reduce the likelihood of error) for prescribing antimicrobials for paediatric community-acquired pneumonia, prospective audit of prescriptions, and healthcare staff training. The data were statistically processed using MedStat v.5.2 software with Student’s t-test for independent samples. Following the interventions, the average hospital stay significantly decreased from 9.48 ± 0.77 days to 6.8 ± 0.34 days (p < 0.001). A reduction was observed in in children under 5 years of age (from 9.9 ± 0.83 to 6.23 ± 0.59 days, p < 0.001), and a downward trend was noted in patients 5 years of age and older (from 8.78 ± 1.57 to 7.03 ± 0.42 days, p = 0.035). The proportion of short-term hospitalizations (up to 7 days) increased from 10.4% to 33.3% (p = 0.003), while prolonged stays over 10 days decreased from 35.4% to 2.2% (p < 0.001). The results demonstrate a positive impact of implemented antimicrobial interventions on the duration of hospitalization in paediatric patients with community-acquired pneumonia. The study supports the rationale for systematic integration of antimicrobial stewardship practices in healthcare facilities as an effective clinical and potentially cost-efficient approach to improving the quality of care.